Unveiling the Enigmatic Code Hero: A Visual Journey within ’Moth Smoke’ by Mohsin Hamid - Hamza, Amir; Wasti, Afia Tasneem; Hassan, Syed Sabih Ul (Pakistan Languages and Humanities Review, 2023)
In this study researchers intended to explore the typical images of Hemingway’s code hero in the novel ‘Moth Smoke’ by Mohsin Hamid. Mohsin Hamid is one of the well-known novelists. His modern writing style exiles him in writing field. The purpose of this article is to find characteristics of Heminway’s code hero in Mohsin Hamid’s works. For this purpose researchers selected Moth Smoke, the first novel of Mohsin Hamid. Close reading technique was adopted for data collection. The main character is Darashikoh Shehzad who displays the typical image of code hero. It shows qualities of grace under pressure including men confronting challenges and showing firm determination and courage while encountering defeat and struggling alone to counterfeit those challenges. At the end Daru, hero of novel was sentenced to death but he never bowed down showing the quality of being destroyed but not defeated.